LA PROTECCIÓN DE LOS ALIMENTARIOS HASTA LA CULMINACIÓN DE SU CARRERA UNIVERSITARIA O TECNOLÓGICA - Ramirez Ato, Jonathan Stalin (2019)
The present thesis constitutes the final report of the investigation process carried out in accordance with article 39 of the Constitution of the Republic which stipulates that the State shall recognize young people as strategic actors in the development of the country, and will guarantee them education, health, housing, recreation, sport, leisure time, freedom of expression and association. The State will promote their employability under fair and dignified conditions, with emphasis on training, ensuring access to first employment and promoting their entrepreneurship skills. The State of Ecuador guarantees the right to education for all young people in the country at all levels. On the other hand, as it is stated in the law the children and adolescents code the state grants the right to people up to the age of 21, when they prove that they are studying at any level of education, and that it prevents or makes it difficult for them to engage in the productive activity, and lacking their own and sufficient resources. It is the duty of their parents to protect their children; however, they are only entitled of this right for people up to 21 years of age. Despite the fact that in our country there are many young people who continue their higher education through long careers, the preparation of which does not allow them to have the necessary time to engage in some productive activity, so that they could be able to cover their expenses. As a result of that I consider that it is necessary to extend the payment of child support by parents to their children until they obtain a professional degree provided by a university. In addition, the above mentioned allow us to understand the legal issue; which is contained in conceptual and doctrinal elements. As a result I propose, that the law grant child support until the conclusion of a bachelor or technical degree; all of this under the condition of responsible studies and the impossibility of providing for themselves. This must be proven by a certificate of successfully completed each scholar term.